Developing Two-Tier Essay for Diagnostic Test Instrument to Identify Student Learning Difficulty - Bagas Abiyyu Pratama; Bambang Subali; Pratiwi Dwijananti (Scientiae Educatia: Jurnal Pendidikan Sains, 2018)
The purpose of this study was to develop a two-tier essay diagnostic test instrument (DTTE) to identify students' learning difficulties. The research adopted by Borg and Gall stages with data collection techniques used are interviews and tests. In the development, there were five valid items DTTE with material feasibility (100%), construction (95,5%), and language (100%). The development results showed the instrument reliability criteria using Cronbach's Alpha (0.76) for the limited trial and field test (0.81). Based on these results DTTE instruments meet the criteria of good, valid and reliable. Analysis of students' learning difficulties based on learning purpose, they are understanding the kinetic and potential energy, able to explain the influence of angle on work, able to explain the work sense in the graph, andÂ  understanding the effort by various styles, to understand relationship work with kinetic energy, with potential energy, and understand conservation of mechanical energy is 92.6%, 90.5%, 89.4%, 89.4%, and 91.5%.